Does board diversity attract foreign institutional ownership? Insights from the Chinese equity market - Shoukat Ali; Ramiz Ur Rehman; Muhammad Ishfaq Ahmad; Joe Ueng (Journal of Risk and Financial Management, 2021)
The study aimed to empirically investigate the impact of board diversity variables (age, gender, nationality, education, tenure, and expertise) on the investment preferences of foreign institutional investors in an emerging market, China. For this, sample data consisted of 1374 nonfinancial Chinese firms from 2009 to 2018. The study used OLS regression as a baseline regression, a fixed effect model to control omitted variable bias, and the two-step systems GMM model to control the endogeneity problem. The study revealed that board diversity variables (gender, nationality, education, and financial expertise) are positively associated with foreign institutional ownership in Chinese nonfinancial firms, implying that foreign institutional investors own a high percentage of Chinese nonfinancial firms with diversity of gender, nationality, education, and financial expertise. Age and tenure of board diversity, on the other hand, have little correlation with foreign institutional ownership. Further, the robustness regressions also confirmed the relationship between board diversity and foreign institutional ownership. This study made a unique attempt to provide empirical evidence that firms having diverse boards attract foreign institutional ownership by reducing asymmetric information.
Keywords: 330; board diversity; foreign institutional ownership; signaling theory; gender equality